Early Childhood Educators on Parental Involvement: A Comparison between Finland and Turkey - Hakyemez-Paul Sevcan; Lähteenmäki Marko; Pihlaja Päivi (Suomen Varhaiskavatus, 2022)
The aim of this study was to analyse the similarities and differences between the views of early childhood educators on parental involvement and their parental involvement practices in Finland and Turkey. Previous studies have indicated a gap between the rhetoric and practice of parental involvement practices and of insufficient parental involvement. In this study, the reasons for these insufficient practices were also investigated. A binary comparison was applied between Turkey and Finland. A questionnaire was developed based on Epstein’s overlapping spheres of influence model. Altogether 515 early childhood educators from Helsinki and Ankara completed this comprehensive questionnaire. Quantitative methods were used for data analysis. The results showed that Turkish and Finnish early childhood educators have positive views on parental involvement, but Turkish early childhood educators implement all types of parental involvement with significantly greater frequency than their Finnish colleagues.